Compare the Efficacy and Safety of SAPB with Continuous Tea in Patients Undergoing Open Lung Resection - Faheem Asghar, Umar Iqbal, Mamoona Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Serratus anterior plane block (SAPB) combined with continuous thoracic epidural analgesia (TEA) is the primary goal of our research. Study Design: Randomized Controlled Trial Place and Duration: Conducted at M.Islam Medical College Gujranwala/Rashid Latif Medical College Lahore, during from June 2021 to Dec 2021. Methods: There were one hundred and six patients of both genders were presented in this study. Patients were aged between 18-65 years.After obtaining written agreement, the demographics of enrolled patients were recorded, including their age, gender, and BMI.Patients were underwent for elective thoracotomy for lung cancer surgery. Patients were equally divided into two groups. A thoracic epidural catheter (10 ml levobupivacaine 0.25 percent followed by 5 ml/hour of 0.125 percent) was given to group II, and a SAPB (30 ml levobupivacaine 0.25 percent followed by 5 ml/hour of 0.125 percent) was given to group I. In order to assess pain, the researchers utilized a visual analogue scale (VAS). The post-operative results of both groups were compared to each other. The full data set was analyzed using the SPSS 24.0 edition. Results:We found majority of the patients 66 (62.3%) were males and 40 (37.7%) cases were females with mean age 50.2±4.42 years. Mean body mass index of the cases were 24.7±6.33kg/m2. In both groups majority of the patients 35 (66.03%) and 36 (67.9%) had ASA class III. Mean operative time in group I was greater 132.8±8.75 minutes as compared to group II 124.3±9.55 minutes. Mean pain score in group I was lower 40.6±5.21 as compared to group II 65.3±4.31. Mean VAS time of coughing was greater in group II of 76.7±1.44 than that of group I 66.2±7.37 cm·h. Analgesic usage was significantly reduced in group I, and the incidence of nausea and vomiting was significantly reduced, with no change in the rate of hypotension between the two groups. Conclusion: In this trial, we found that continuous SAPB was more effective than TEA in reducing postoperative pain in patients following open lung resection for cancer, andcomplications were reduced in the SAPB group.